How media remembered the past: framing analysis of the may 1998 tragedy in Indonesian print newspapers (1999-2008) - Doddy Salman; Andrik Purwasito; Wakit Abdullah Rais (Penerbit Universiti Kebangsaan Malaysia, 2023)
The purpose of this study is to examine the news framing of a national tragedy in three Indonesian newspapers i.e., Kompas, Suara Karya and Republika from 1999 to 2008. The news was selected based on a purposive sampling of these newspapers published every May from 1999 to 2008 during the anniversary of the May 1998 tragedy. By using Robert N. Entman’s framing theory, the findings found that Kompas, Republika, and Suara Karya dominantly framed their news coverage of the tragedy on the following four elements, i.e., the tragedy of humanity, intellectual actors, victims’ suffering, and post-tragedy events. The legal issues as the main point of resolving the May 1998 tragedy were ignored in the news. The recommendations to interrogate the actors summoned by the Joint Fact Finding Team (Tim Gabungan Pencari Fakta/TGPF) for the May 1998 tragedy were never mentioned in the news. These news reports put the victims and their families as victims of individual action, not as victims of structural crimes. In addition, the recommendation produced by these newspapers after the tragedy is predominantly to strengthen solidarity with the victims and their families, not to prosecute the cases legally. In conclusion, these news media are believed to be conscious of not getting to the May 1998 tragedy as there is no political interest of the Indonesian government to resolve the tragedy.